2014
DOI: 10.1007/s11605-014-2552-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Morgagni Hernia Repair: How I Do It

Abstract: Surgical repair of Morgagni hernias is recommended given their historically high risk of incarceration. Traditionally, such repair has been undertaken via laparotomy or thoracotomy or more recently, thoracoscopically or laparoscopically using mesh. Here, we describe a laparoscopic approach to the management of Morgagni hernias achieving a primary tissue repair without mesh implantation. This technique allows for the general benefits of minimally invasive surgery, such as less postoperative pain, reduced wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 15 publications
0
34
0
3
Order By: Relevance
“…As advantages, they offer a better view of the surgical ield, easy reduction of the hernia contents, the possibility of simple closing or the use of mesh, and the surgery is less aggressive, decreasing postoperative pain and the length of the hospital stay [2,3,7,8,9,11]. The post-operative complications described in the bibliography are: Atelectasis with serious respiratory insuf iciency, pneumothorax, pneumomediastinum, subcutaneous emphysema, CO2 embolism (in laparoscopic surgery techniques) and reappearance of the hernia, among others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As advantages, they offer a better view of the surgical ield, easy reduction of the hernia contents, the possibility of simple closing or the use of mesh, and the surgery is less aggressive, decreasing postoperative pain and the length of the hospital stay [2,3,7,8,9,11]. The post-operative complications described in the bibliography are: Atelectasis with serious respiratory insuf iciency, pneumothorax, pneumomediastinum, subcutaneous emphysema, CO2 embolism (in laparoscopic surgery techniques) and reappearance of the hernia, among others.…”
Section: Discussionmentioning
confidence: 99%
“…Its treatment is surgical, and the classic approach is a laparotomy, and more rarely, thoracotomy, but in recent years, several procedures using laparoscopy or thoracoscopy [7][8][9], have been described. There is little experience because of the infrequency of the pathology.…”
Section: Introductionmentioning
confidence: 99%
“…The abdominal approach can provide excellent exposure to allow full exploration of the hernia sac and bilateral diaphragm, provide easier access when narrowing the hernia defect, and allow for simultaneously performing other procedures such as fundoplication. 5,8) There are two common methods used to repair the MH defect. Some surgeons use plastic meshes to reach a tension-free repair.…”
Section: Discussionmentioning
confidence: 99%
“…Others prefer to narrow the hernia defect with nonabsorbable sutures directly as a safe and effective method. 7,8) Management of the hernia sac is controversial because the natural history of an unexcised hernia still remains unclear. Some surgeons think that removing the sac is not necessary and the risk of injuring thoracic structures due to intrathoracic adhesions is high, while others think resection of the sac is safe and adhere more strictly to classic surgical principles of hernia repair.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that mesh repair for MH could be performed via laparotomy, thoracotomy and thoracoabdominal approach, but mesh insertion was not always necessary for diaphragmatic hernia (3,4). On the contrary, a retrospective review indicated that MH recurrence was high after laparoscopic repair in patients without patch, and more frequent use of patch may be beneficial (5).…”
Section: Discussionmentioning
confidence: 99%